Principles of radiological protection and application of ALARA, ALADA, and ALADAIP: a critical review - Mendonça, Rafael Pereira de; Estrela, Carlos; Bueno, Mike Reis; Carvalho, Teresa Cristina Alves Silva Gonzalez; Estrela, Lucas Rodrigues de Araújo [UNESP]; Chilvarquer, Israel (FapUNIFESP (SciELO), 2025)
This study carried out a critical review of the principles of radioprotection, including the ALARA, ALADA, and ALADAIP principles. The Google Scholar and PubMed databases were the search resources, and the following keywords were searched: Linear No-Threshold (LNT); Biologic Effects of Ionizing Radiation (BEIR VII); As Low As Reasonably Achievable (ALARA); As Low As Diagnostically Acceptable (ALADA); As Low As Diagnostically Acceptable, being Indication-oriented and Patient-specific (ALADAIP). This critical review included studies with historical references, reviews, position papers, and clinical and experimental studies. Regarding data extraction, only original articles were selected after the screening process. Much of the current evolution of X-ray machines and radioprotection protocols has stemmed from legitimate concerns about this topic. This development has grown out of the relevant work of organizations like ICRP, UNSCEAR, and other renowned international organizations. Low doses of radiation, such as those used for diagnosis, also occur naturally and are present in everyday life. Although there is no agreement on the actual risk involving low doses, the recommendations of ALARA, ALADA, and ALADAIP prevail, in line with the trend to uphold principles that balance the importance of X-ray diagnostic imaging with the intention of keeping the doses as low as possible. The benefits of X-ray exams, when justified, tend to outweigh the low risks attributed to them.
Keywords: Radiation; Radiation Protection; Radiology